Cryptate mediated nucleophilic 18F-fluorination without azeotropic drying - Wessmann, S. H.; Henriksen, G.; Wester, H.-J. (Nuklearmedizin - NuclearMedicine, 2012)
The radiosynthesis of the vast majority of 18F-labeled tracers rely on azeotropic drying of [18F]fluoride and subsequent cryptate mediated introduction of [18F]fluoride by nucleophilic substitution. The aim of this study was to develop a method for simplification of this process, based on preparation of reactive [K+⊂2.2.2]18F- by solvent drying of [18F]fluoride adsorbed onto an anion exchange resin. Methods: Aqueous [18F]fluoride (0.5–1 ml) obtained from the 18O(p,n)18F nuclear reaction was trapped on a strong anion-exchange (SAX) cartridge. After washing the cartridge with dry CH3CN, [18F]fluoride was eluted with an anhydrous solution of [K+⊂2.2.2]OH- in CH3CN and directly used for nucleophilic fluorination reactions. Results: [18F]Fluoride from target water was quantitatively retained by the SAX cartridge, and water-free [18F] − fluoride recovered in an overall yield of 92 ± 5% (n = 10). [18F]Fluoride obtained by this procedure led to radiochemical yields of 70–90% for [18F]FDG, [18F]FET, [18F]FLT, [18F]FAZA and [18F]Fallypride. Conclusion: SAXresin adsorbed [18F]fluoride can be dried with non-aqueous solvents and eluted with [K+⊂2.2.2]OH- in CH3CN. The reactivity of [K+⊂2.2.2]F- generated by the new method is comparable to that of [18F]fluoride obtained by azeotropic drying. The described procedure facilitates the automated production of 18F-radiopharmaceuticals in general, and may also simplify the use of microfluidic devices for 18F-radiotracer production.
Keywords: [18F]fluoride; 18F-fluorination; production PET; radiopharmaceutical